BLOOD GLUCOSE RESPONSE AND GLYCEMIC INDEX OF BREADS AND SOME WHEAT PRODUCTS IN NORMAL HUMAN SUBJECTS - Abdullah M. Thannoun (Mesopotamia Journal of Agriculture)
Blood glucose response and glycemic Index (GI) for whole wheat loaf, white flour loaf and white flour bread "Tannour bread" and wheat products such as burghul, habbiyah, reshta and spaghetti in normal human subjects using glucose as standard were studied. Twenty one normal male human subjects (age 22-35 years and body mass index, BMI 22-26 kg/m²) were chosen as volunteers for this study. The subjects were divided randomly into seven groups where each three of the subjects could submit to the experiments. After 12 hours overnight fast, each subject was tested for blood glucose at zero time before given the test food or glucose standard in an amount to provide 50 g carbohydrate. Glycemic response, Incremental Area Under the Curve (IAUC) and Glycemic index (GI) were determined and calculated. The results showed that there were no significant (P<0.05) differences in GI between the three kinds of breads (61, 69 and 64 for each whole wheat loaf, white flour loaf and white flour Tannour bread, respectively), however, there were a significant (P<0.05) differences between each kind of bread and glucose standard (100). Further, the GI values of all kinds of bread were higher than that of other wheat products (41, 40, 26 and 40 for burghul, habbiyah, reshta and spaghetti, respectively). It was concluded that food processing method including changing in food components of the product resulted in variable blood glucose response. It was also concluded that the above wheat products could be used efficiently in diet management of Type II diabetes.